Instructional design and e-learning: examining learners’ perspective in Malaysian institutions of higher learning - Hussin, Husnayati; Bunyarit, Fatimah Sumet; Hussein, Ramlah (Emerald, 2009)
Purpose – This study aims to investigate the elements of effective instructional design in an e-learning environment in selected Malaysian higher learning institutions. In addition, the study also seeks to investigate the e-learning use behaviour among these e-learners.